More Versus Better: Artificial Intelligence, Incentives, and the Emerging Crisis in Peer Review - Gartenberg, Claudine; Hasan, Sharique; Murray, Alex; Pierce, Lamar (Organization Science, 2026)
As the AI Task Force for Organization Science, we provide an early account of artificial intelligence’s (AI) impact on both submissions and reviews at a major academic journal. Submission volume has risen 42% since the late 2022 release of ChatGPT, while writing quality has declined. The rise in AI-generated writing accounts for nearly all of these trends. AI-generated writing in reviews has also increased, and is characterized by lower writing quality and less topical diversity than human-generated writing. We are, to our knowledge, the first journal to report these early impacts of AI in the review process. Conversations with editors across scientific disciplines, however, suggest that what we observe is not limited to our journal or to the social sciences. At this early stage of AI adoption, we cannot make a normative assessment about appropriate or ideal levels of AI usage. We can, however, conclude that the current state of AI tools, amplified by existing publish-or-perish incentives, appears to be pushing the system toward an equilibrium of more rather than better research. Reaching an equilibrium in which AI serves as a critical engine of innovation will require that our institutions and the incentive structures they create adapt. Funding: S. Hasan used research funding from Duke University’s Fuqua School of Business. C. Gartenberg used research funding from University of Pennsylvania’s Wharton School. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2026.ed.v37.n3 .